The Qumran paradigm: a critical evaluation of some foundational hypotheses in the construction of the Qumran sect - Looijer, Gwynned de (Society of Biblical Literature. Early Judaism and its literature, 2015)
Cover; Contents; Acknowledgments; Abbreviations; Figures and Tables; 1. Introduction; 2. Textual Classifications of Presectarianism; 3. The Provenance of 4QMMT; 4. Ideology as a Cohesive Strategy; 5. The Zenith of Qumran Thought; 6. The Qumran Paradigm; Bibliography; Index of Primary Texts; Index of Modern Authors.